U1 snRNA interactions with deep intronic sequences regulate splicing of multiple exons of spinal muscular atrophy genes - Ottesen, Eric W.; Singh, Natalia N.; Seo, Joonbae; Singh, Ravindra N. (Frontiers in Neuroscience, 2024)
The U1 small nuclear RNA (snRNA) forms ribonucleoprotein particles (RNPs) such as U1 snRNP and U1-TAF15 snRNP. U1 snRNP is one of the most studied RNPs due to its critical role in pre-mRNA splicing in defining the 5' splice site (5'ss) of every exon through direct interactions with sequences at exon/intron junctions. Recent reports support the role of U1 snRNP in all steps of transcription, namely initiation, elongation, and termination. Functions of U1-TAF15 snRNP are less understood, though it associates with the transcription machinery and may modulate pre-mRNA splicing by interacting with the 5'ss and/or 5'ss-like sequences within the pre-mRNA. An anti-U1 antisense oligonucleotide (ASO) that sequesters the 5' end of U1 snRNA inhibits the functions of U1 snRNP, including transcription and splicing. However, it is not known if the inhibition of U1 snRNP influences post-transcriptional regulation of pre-mRNA splicing through deep intronic sequences. Here we examined the effect of an anti-U1 ASO that sequesters the 5' end of U1 snRNA on transcription and splicing of all internal exons of the spinal muscular atrophy (SMA) genes, SMN1 and SMN2. Our study was enabled by the employment of a multi-exon-skipping detection assay (MESDA) that discriminates against prematurely terminated transcripts. We employed an SMN2 super minigene to determine if anti-U1 ASO differently affects splicing in the context of truncated introns. Our results uncover a unique role of the U1 snRNA-associated RNPs in splicing regulation executed through deep intronic sequences. Findings are significant for developing novel therapies for SMA based on deep intronic targets.